Numerical Simulation of Transmission LineIcing Based on Computational Fluid Dynamics - Liu, Junxiang; Xu, Zhong; Fan, Weinan; Wang, Yong; Mo, Wenxiong (Journal of physics. Conference series, 2022)
In recent years, transmission line icing disasters occur frequently, which poses a great threat to the operation of power grid. Most of the existing studies do not consider the impact of time-varying meteorological conditions on conductor icing. In order to effectively predict the growth of line icing, it provides an important reference for transmission line deicing and galloping early warning. The wind tunnel model of the transmission line is established by using the computational fluid dynamics simulation software, and the air flow field distribution around the transmission line is calculated by using the hybrid grid division. By establishing the motion equation of cooling water droplets in the air and analyzing the motion trajectory of water droplets, the local collision coefficient between water droplets and the transmission line is obtained, and the icing surface of the transmission line is discretized into a control body, Through the establishment of thermodynamic model, the mass balance and energy balance equations are established to calculate the icing quality of transmission line. According to the environmental temperature, wind speed, transmission line diameter and other factors, the quantitative influence degree of different factors on the icing form of transmission line is output, so as to provide technical support for the safe and stable operation of important transmission channels.